Epiblastic Cited2 deficiency results in cardiac phenotypic heterogeneity and provides a mechanism for haploinsufficiency. - MacDonald, S; Bamforth, S; Chen, C; Farthing, C; Franklyn, A; Broadbent, C; Schneider, J; Saga, Y; Lewandoski, M; Bhattacharya, S (2008)
AIMS: Deletion of the transcription factor Cited2 causes penetrant and phenotypically heterogenous cardiovascular and laterality defects and adrenal agenesis. Heterozygous human CITED2 mutation is associated with congenital heart disease, suggesting haploinsufficiency. Cited2 functions partly via a Nodal-->Pitx2c pathway controlling left-right patterning. In this present study we investigated the primary site of Cited2 function and mechanisms of haploinsufficiency. METHODS AND RESULTS: A Cited2 conditional allele enabled its deletion in particular cell lineages in mouse development. A lacZ reporter cassette allowed indication of deletion. Congenic Cited2 heterozygous mice were used to investigate haploinsufficiency. Embryos were examined by magnetic resonance imaging, by sectioning and by quantitative real-time polymerase chain reaction (qRT-PCR). Epiblast-specific deletion of Cited2 using Sox2Cre recapitulated penetrant and phenotypically heterogenous cardiovascular and laterality defects. Neural crest-specific deletion using Wnt1Cre affected cranial ganglia but not cardiac development. Mesodermal deletion with Mesp1Cre resulted in low penetrance of septal defect. Mesodermal deletion with T-Cre resulted in adrenal agenesis, but infrequent cardiac septal and laterality defects. beta-Galatactosidase staining and qRT-PCR demonstrated the efficiency and location of Cited2 deletion. Murine Cited2 heterozygosity is itself associated with cardiac malformation, with three of 45 embryos showing ventricular septal defect. Cited2 gene expression in E13.5 hearts was reduced 2.13-fold in Cited2(+/-) compared with wild-type (P = 2.62 x 10(-6)). The Cited2 target gene Pitx2c was reduced 1.5-fold in Cited2(+/-) (P = 0.038) hearts compared with wild-type, and reduced 4.9-fold in Cited2(-/-) hearts (P = 0.00031). Pitx2c levels were reduced two-fold (P = 0.009) in Cited2(+/-) embryos, in comparison with wild-type. Cited2 and Pitx2c expression were strongly correlated in wild-type and Cited2(+/-) hearts (Pearson rank correlation = 0.68, P = 0.0009). Cited2 expression was reduced 7474-fold in Sox2Cre deleted hearts compared with controls (P = 0.00017) and Pitx2c was reduced 3.1-fold (P = 0.013). Deletion of Cited2 with Mesp1Cre resulted in a 130-fold reduction in cardiac Cited2 expression compared with control (P = 0.0002), but Pitx2c expression was not affected. CONCLUSION: These results indicate that phenotypically heterogenous and penetrant cardiac malformations in Cited2 deficiency arise from a primary requirement in epiblast derivatives for left-right patterning, with a secondary cell-autonomous role in the mesoderm. Cardiac malformation associated with Cited2 haploinsufficiency may occur by reducing expression of key Cited2 targets such as Pitx2c.